Detoxification of Cadmium on Albino Rats (Rattus norvegicus) with Natural Chelator of Fruiting Body Extract of Ganoderma lucidum - Hameda Dhaka Kusuma Taufiq; Hernayanti Hernayanti; Nuniek Ina Ratnaningtyas (Molekul, 2023)
Cadmium is a heavy metal pollutant sourced from various industries and toxic to the kidneys. Cadmium exposure can be used natural chelator of ethanol extract of the fruiting body of Ganoderma lucidum. The aim of the study was to determine the effect and effective dose of the ethanolic extract of the fruiting body of G. lucidum on reducing the toxicity effect of cadmium in male albino rats (Rattus norvegicus) Wistar strain. The research design was experimental research, which consisted of 5 treatment levels. The research parameters were blood cadmium, β2-microglobulin, malondialdehyde, and superoxide dismutase levels. The ethanolic extract of fruiting body of G. lucidum was tested by gas chromatography-mass spectrometry (GCMS) to determine linalool as active compounds. The results of each parameter had a significant effect, which decreased blood cadmium, β2M and MDA levels, and increased SOD level that linear according to the addition of the dose of ethanol extract of the fruiting body of G. lucidum. Blood cadmium levels with β2M and MDA levels had a positive correlation, while blood cadmium levels with SOD levels had a negative correlation. The dominant compound detected was linalool which has potential as a radical scavenger. The dose of 750 mg.kgBW-1 is the effective dose of the ethanolic extract of fruiting body of G. lucidum based on a decrease in blood cadmium levels (54.10%), β2M (63.94%) and MDA (20.31%), as well as an increase in SOD levels (14.20%) compared to sick control.